Sign Consumption and Fetishism Behind the Hyperreality of Plant Collection Trends During a Pandemic - Listianti, Feny (Bina Nusantara University, 2022)
The research aimed to understand the process of sign consumption behind ornamental plant collection activities, fetishism towards plant aesthetics, and the hyperreality of ornamental plant collection lifestyle mediated by social media. The nurturing plantsâ€™ activity initially aimed to improve the fresh air quality and create a more beautiful environment that had now shifted to showing social status due to the emerging trend during the pandemic. A qualitative approach with multimodal analysis, purposive sampling, and constructivism paradigm was implemented. Three Instagram accounts of ornamental plant collectors were analyzed and interpreted through text, images, and videos. After that, the researcher constructed the finding into themes by comparing selected Instagram accounts to ensure reliability and validity. The results show that the value of plants is now shifting into a lifestyle where they are used as objects that should be shown to others. Social media boosts this ornamental plant collection trend widespread, creating hyperreality and making collectors trapped in fetishism. Academically, this research emphasizes Instagramâ€™s role in spreading sign consumption, fetishism, hyperreality, and consumerism massively. Further research can be done by using the interview method with plant collectors to find out their direct experience. The practical implication of the research is to open the horizon of Indonesian people to avoid the trap of lifestyle trends. Another practical implication is for Financial Consultants/Advisors/Planners and Social Movement organizations to educate the public to spend money wisely and create new programs to avoid the consumerism trap even more.Â